Nested PCR reveals elevated over-diagnosis of E. histolytica in Barcelona, Venezuela. - Rodulfo, Hectorina; Ahmar, Beatriz; Rodríguez, María; Mora, Leonor; De Donato, Marcos (Investigación Clínica, 2012)
The aim of this study was to identify the presence of Entamoeba histolytica and E. dispar by nested PCR in children attending the “Dr. Luis Razetti” Hospital, Barcelona, Anzoátegui State. Of the 1,141 fecal samples coproparasitologically evaluated by conventional microscopy, 150 were diagnosed positive for E. histolytica in 0-10 year-old-children, of both sexes. The signs, symptoms and a full coproparasitological report were ob- tained from all of these and nested PCR was performed to identify E. histolytica and E. dispar. The conventional microscopy results showed a diag- nostic frequency of E. histolytica in 13.2% of the cases, of which 79.3% were positive only for this pathogen. However, nested PCR showed that of these, only 28% (42/150) were actually infected by Entamoeba spp., revealing a high over-diagnosis of E. histolytica. We also identified 9.3% E. histolytica, 4% E. dispar and 4.7% mixed infections. Diarrhea was the most common symptom, followed by abdominal pain and fever. Bloody stools were statistically associ- ated with E. histolytica, but were also found for E. dispar infections. This study demonstrates that molecular techniques complementary to conven- tional methods enable the correct identification of Entamoeba spp., thus con- tributing to an improved epidemiological assessment of these parasites and implementation of the appropriate treatment.